Implementation of recommendations in rheumatic and musculoskeletal diseases: considerations for development and uptake. Issue 10 (12th August 2022) - Loza, Estibaliz; Carmona, Loreto; Woolf, Anthony; Fautrel, Bruno; Courvoisier, Delphine S; Verstappen, Suzanne; Aarrestad Provan, Sella; Boonen, Annelies; Vliet Vlieland, Thea; Marchiori, Francesca; Jasinski, Tiina; Van der Elst, Kristien; et al.
Abstract : A clinical guideline is a document with the aim of guiding decisions based on evidence regarding diagnosis, management and treatment in specific areas of healthcare. Specific to rheumatic and musculoskeletal diseases (RMDs), adherence to clinical guidelines recommendations impacts the outcomes of people with these diseases. However, currently, the implementation of recommendations is less than optimal in rheumatology. The WHO has described the implementation of evidence-based recommendations as one of the greatest challenges facing the global health community and has identified the importance of scaling up these recommendations. But closing the evidence-to-practice gap is often complex, time-consuming and difficult. In this context, the implementation science offers a framework to overcome this scenario. This article describes the principles of implementation science to facilitate and optimise the implementation of clinical recommendations in RMDs. Embedding implementation science methods and techniques into recommendation development and daily practice can help maximise the likelihood that implementation is successful in improving the quality of healthcare and healthcare services.